The regulation of artificial intelligence for health in Brazil begins with the General Personal Data Protection Law - Daniel de Araujo Dourado; Fernando Mussa Abujamra Aith (Universidade de São Paulo, 2022)
ABSTRACT Artificial intelligence develops rapidly and health is one of the areas where new technologies in this field are most promising. The use of artificial intelligence can modify the way health care and self-care are provided, besides influencing the organization of health systems. Therefore, the regulation of artificial intelligence in healthcare is an emerging and essential topic. Specific laws and regulations are being developed around the world. In Brazil, the starting point of this regulation is the Lei Geral de Proteção de Dados Pessoais (LGPD - General Personal Data Protection Law), which recognizes the right to explanation and review of automated decisions. Discussing the scope of this right is needed, considering the necessary instrumentalization of transparency in the use of artificial intelligence for health and the currently existing limits, such as the black-box system inherent to algorithms and the trade-off between explainability and accuracy of automated systems.